Strengthening regional public library services through P3KNK experiential learning community service - Alya Hafizza (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
Public libraries play a strategic role as centers for lifelong learning, strengthening information literacy, and developing the quality of human resources at the community level. This community service activity is implemented through the Program Penguatan Profesi Kepustakawanan Non-Kependidikan (P3KNK) in response to limited human resources and suboptimal services at regional public libraries. Through experiential learning, this program positions students as service actors directly involved in core library activities, thus functioning not only as interns but also as partners in service strengthening. A qualitative descriptive approach is used to analyze the process and impact of program implementation through participant observation, documentation, and reflective notes. The results show that direct student involvement can enhance students' professional competence and make a meaningful contribution to collection management, service effectiveness, and managerial support at partner libraries. The novelty of this activity lies in the integration of P3KNK as an experiential learning-based service model that simultaneously links student competency strengthening with the real needs of regional public libraries, resulting in dual benefits for educational institutions and the community. These findings confirm that P3KNK has the potential to serve as a model for applicable, contextual, and sustainable librarianship services that strengthen community-based library services.   Abstrak Perpustakaan umum memiliki peran strategis sebagai pusat pembelajaran sepanjang hayat, penguatan literasi informasi, serta pengembangan kualitas sumber daya manusia di tingkat masyarakat. Kegiatan pengabdian kepada masyarakat ini dilaksanakan melalui Program Penguatan Profesi Kepustakawanan Non-Kependidikan (P3KNK) sebagai respons terhadap keterbatasan sumber daya manusia dan belum optimalnya layanan pada perpustakaan umum daerah. Melalui pembelajaran berbasis pengalaman (experiential learning), program ini menempatkan mahasiswa sebagai aktor pengabdian yang terlibat langsung dalam aktivitas inti perpustakaan, sehingga tidak hanya berfungsi sebagai peserta magang, tetapi sebagai mitra penguatan layanan. Pendekatan deskriptif kualitatif digunakan untuk menganalisis proses dan dampak pelaksanaan program melalui observasi partisipatif, dokumentasi, dan catatan reflektif. Hasil menunjukkan bahwa keterlibatan mahasiswa secara langsung mampu meningkatkan kompetensi profesional mahasiswa sekaligus memberikan kontribusi nyata terhadap perbaikan pengelolaan koleksi, efektivitas layanan, dan dukungan manajerial perpustakaan mitra. Kebaruan kegiatan ini terletak pada integrasi P3KNK sebagai model pengabdian berbasis experiential learning yang mengaitkan penguatan kompetensi mahasiswa dengan kebutuhan nyata perpustakaan umum daerah secara simultan, sehingga menghasilkan manfaat ganda bagi institusi pendidikan dan masyarakat. Temuan ini menegaskan bahwa P3KNK berpotensi menjadi model pengabdian kepustakawanan yang aplikatif, kontekstual, dan berkelanjutan dalam penguatan layanan perpustakaan berbasis komunitas. Kata Kunci: kompetensi kepustakawanan; pengabdian kepada masyarakat; perpustakaan umum